The transition into adoptive parenthood: Adoption as a process of continued unsafe uncertainty when family scripts collide. (October 2016) - Tasker, Fiona; Wood, Sally
Our prospective study investigated couples' expectations of adoptive parenthood and explored how these changed with their actual experience of parenthood. Six heterosexual couples were interviewed just before placement began and 6 months after the children had arrived. Interpretative Phenomenological Analysis (IPA) was used to analyse both sets of interview data. Expectations of adoptive parenthood mostly transformed smoothly into adoption experience for couples, but challenges were experienced when family scripts collided and a continued feeling of unsafe uncertainty then prevailed within these newly formed family systems. Family script collision seemed a particular problem for couples adopting sibling pairs. To further professional practice in working with families over the transition to adoptive parenting, we suggest that professionals keep in mind a framework that includes the following: Internal and external world influences on family members, Intergenerational issues, Family scripts and the Structural challenges of adoption (IIFS).